Contralateral biopsies in patients with testicular germ cell tumours: patterns of care in Germany and recent data regarding prevalence and treatment of testicular intra‐epithelial neoplasia. (22nd August 2014) - Ruf, C.G.; Gnoss, A.; Hartmann, M.; Matthies, C.; Anheuser, P.; Loy, V.; Pichlmeier, U.; Dieckmann, K.‐P.
Summary The precursor of testicular germ cell tumours (GCTs), called testicular intra‐epithelial neoplasia (TIN/CIS), is safely diagnosed immunohistologically. Testicular biopsy provides a valuable tool for early detection of GCTs in risk groups. Although this knowledge is undisputed, testicular biopsies are utilized poorly. The patterns of care regarding the use of biopsies remain unknown. Uncertainty exists about the prevalence and specific treatment of TIN/CIS. We asked clinical urologists in Germany whether or not they employed contralateral biopsies in GCT patients. We evaluated the prevalence of contralateral TIN/CIS in a retrospective analysis of 780 consecutive GCT patients. All had contralateral double biopsies. Discordance of TIN/CIS findings among biopsy pairs as well as age, histology of the primary tumour and clinical stage was noted. Evaluation of data comprised descriptive statistical methods. To evaluate treatment options for TIN/CIS, we performed a literature search. 52.1% of German urologists always perform the biopsy, 17% do it mostly, 27.3% in select cases, 3.5% never. Curiously, there was a geographic north‐south gradient regarding biopsy use. Contralateral TIN/CIS was found in 5%. The median ages of patients with TIN/CIS and those without were 31.8 and 34.9 years respectively (p = 0.02). The discordance rate among biopsy pairs was of 33%. Two‐site biopsies provide a 17% gain in diagnostic sensitivity. Local radiotherapy with 20 Gy is the safest treatment of TIN/CIS failing in 2%. Chemotherapy has significantly lower efficacy. Contralateral testicular biopsies in GCT patients are well accepted among German urologists. The prevalence of contralateral TIN/CIS found in this series is in accordance with previous reports. Double biopsies should be the diagnostic standard because of their diagnostic superiority. Local radiotherapy with 20 Gy is the safest way of eradicating TIN/CIS. Failures occur in only 2%, usually many years after irradiation. Cisplatin‐based chemotherapy is dose dependent and less effective.